Pelatihan Mengelola Keuangan Badan Usaha Milik Desa Cijambu Kecamatan Tanjungsari - Sari, Widya; Wardatussaniah, Silpa (Ma'soem University, 2023)
The hope of the community is that BUMDes can help better and professionally manage village potential. However, Cijambu BUMDes experience problems, especially in terms of financial management and making financial statements. This activity uses the PAR (Participatory Action Research) method. Before the PKM activity was held, the author inventoried the problems in Cijambu Village and the things needed by the community. To overcome the problems of BUMDes in Cijambu Village, in the seminar, the author gave directions on how to record financial transactions and steps to make financial statements in accordance with BUMDes. By referring to Financial Accounting Standards for Micro, Small and Medium Entities, which can also be applied by MSME actors in Cijambu village. The results of the activity showed that participants gained knowledge and information on how to manage finances effectively and efficiently, as well as understand the recording of financial transactions and making financial statements in accordance with BUMDes, so that BUMDes can meet reporting according to regulations.